Studies of Soils and Vegetation on Non-ferrous Metallurgy Slag Dumps - Zolotova, Ekaterina (International Journal of Bio-resource and Stress Management, 2021)
The metallurgical industry is one of the major pollution sources of natural ecosystems. Now the slag dumps of non-ferrous industries occupy huge areas all over the world. The purpose of this literature review was to assess the knowledge degree of the soils and vegetation formed on the non-ferrous metallurgy slag dumps. Most of the research was carried out for the dumps of the copper-smelting (including old dumps) and lead-zinc industries, the dumps of the nickel and aluminum industries have been studied to a lesser extent. The composition of non-ferrous metallurgy slags, the issues of soil pollution with heavy metals, their bioavailability were discussed. The influence of heavy pollution on the biodiversity of pioneer plant communities on the slag dumps of non-ferrous metallurgy and the floristic composition for abandoned copper ore deposits are noted. The experience of Russian scientists in the reclamation of an aluminum sludge dump and Chinese scientists in the reclamation of zinc production slag dumps are considered. The possibility of introducing waste from the copper smelting slag recycling waste into natural ecosystems was discussed. The analysis of literature revealed gaps in knowledge about the gradual formation of the soil and vegetation on man-made landscapes, about the plant biodiversity in conditions of heavy pollution, ways of their adaptation, and the heavy metals accumulation by different plant species.